DEVELOPMENT OF MULTIMODAL LANGUAGE TEACHING MATERIALS FOR INDONESIAN LANGUAGE FOR FOREIGN SPEAKERS (BIPA) DURING PANDEMIC TIME - Dieni Amalia Zamzamy (English Language and Literature International Conference (ELLiC) Proceedings, 2021)
The application of multimodal teaching and learning materials for BIPA has become increasingly more prevalent during the new normal period. As a consequence of various limitations imposed on them due to the lockdown, BIPA teachers are increasingly required by necessity to start producing multimodal teaching and learning materials so BIPA learning can still continue. It should be noted however that this sudden transition of BIPA learning from the initial direct face-to-face mode to an emergency online learning approach, has significantly affected the teachers in writing, compiling, and authoring multimodal materials. Noting such circumstance and predicaments, this literature review research paper aims to examine the modes applied by teachers in compiling teaching and learning materials, to investigate the role of multimodality implemented by teachers in BIPA learning, and to identify the impacts of multimodal teaching and learning materials on students. The results of the research suggest that teachers do have preference of a certain mode in teaching for a particular language competence. Furthermore, multimodal teaching and learning materials have been demonstrated to be able to effectively improve BIPA learning process, making it more attractive, and increase students’ learning interests despite the fact that multimodal teaching and learning materials are in dire need of more attention and have so much room for improvement